Job crafting and its role in fostering personal resources and adaptation to change in the context of a pandemic - Fulvio Signore; Emanuela Ingusci; Elisa De Carlo; Alessia Anna Catalano; Claudio Giovanni Cortese; Enrico Ciavolino; Enrico Ciavolino (Frontiers in Organizational Psychology, 2025)
IntroductionOver the last few decades, various strategies have been investigated, in order to improve workers' wellbeing by empowering workers themselves as agents of change. The individual processes enabling workers to shape their professional context to better suit their needs include job crafting, a bottom-up strategy associated with numerous positive outcomes. The COVID-19 pandemic induced significant changes in the work environment, indirectly prompting workers to find new ways to manage their tasks. This study draws on the theoretical framework provided by the Job Demands-Resources model to examine the relationships between job crafting, job resources—specifically self-efficacy and positive emotions—and strategies to cope with organizational change.MethodsTo achieve this objective, analyses were conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) and validated through 5,000 bootstrap resamples. A sample of 782 workers, selected through non-probabilistic convenience sampling, completed a questionnaire between May and July 2020. Variables measured included personal resources, such as self-efficacy and positive emotions, job crafting, age, and coping with organizational change, assessed via several items drawn from validated scales.ResultsThe findings showed that, during the pandemic, job crafting played a significant role in enhancing personal resources, as defined by the Job Demands-Resources model, promoting growth processes and facilitating adaptation to change.DiscussionFrom a practical perspective, job crafting proved to be an important strategy for activating positive psychological and emotional resources, even during periods of extreme turbulence and transformation. The practical implications and limitations of the study are discussed.